(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article is devoted to the concept of “discourse” contained in linguistics and its oral and written forms, and the article discusses the research work carried out on discourse.